Respon Masyarakat Millenial Tentang Urgensi Menjadi Guru Berkarakter Ikhlas Dalam Perspektif Manajemen Sumber Daya Pendidikan - Mawardi Lubis (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2022)
Abstract: Millennial Society's Response to the Urgency of Becoming a Teacher with a Sincere Character in the Perspective of Educational Resource ManagementThis study aims to describe the millennial community's response to the urgency of teachers with sincere characters from the perspective of educational resource management. The study was conducted in October - November 2022 at Fatmawati Sukarno Bengkulu State Islamic University with a quantitative research type using a survey method. The population of this study were all campus lecturers, employees and students who were born in the year before the 1980s, besides that they were also members of the WhatsApp Group, totaling 383 people with 27.42% of the population (105 people) as respondents. The analysis technique of this research is to use descriptive quantitative analysis techniques with the help of the percentage formula (P = f/N x 100). The results showed that 81.90% of the public agreed with the statement that